Medicine storage allocation in smart pharmacy - Xu, Zhiyong (2019)
The aging population has led to greater pressure on healthcare work in Singapore. As an important medical institution in Singapore, Changi General Hospital attaches great importance to improving the service level for patients, and reducing patients' waiting time for taking medicine is one of the important measures. Under such circumstance, this project uses an optimization method to determine the best drug allocation in the auto dispensing equipment ASRS of the smart pharmacy in Changi General Hospital. The objective is to shorten the total travel distance in the medicine dispensing, so as to minimize patients’ waiting time. In terms of selection methods, “people to goods” and “goods to people” selection methods were compared and analyzed from different aspects through comparative analysis, and it is concluded that “goods to people” selection method was a better method to meet the needs of pharmacy. In addition, the storage allocation principles including shelf stability principle, efficiency principle, and product relevance principle have been discussed and analyzed. From the respect of problem-solving solution, a multi-objective optimization mathematical model is established, and then the weight assignment method and DSM method are applied to solve the optimization problem. In addition, the results of these two methods are calculated by Python, and a comparison between these two methods has been made. The result shows that the feasible solutions obtained by these two methods can effectively shorten the total picking distance, improve the efficiency of ASRS, decrease the waiting time for patients.